Habits of Mind Strategies for Enhancing Students’ Math Problem Solving Skills - Habibi, Mhmd; Lasia, Dwi; Oktafia, Mesi; Ilham, Muhammad (Universitas Muhammadiyah Mataram, 2020)
The objective of this research is to know the differences in mathematical problem solving skills between using mathematical habits of mind strategy with conventional learning. Methods that is used is quasi-experimental, with non-equivalent control group design. The subject of this study was a 7th grade junior high school student with 56 number of people which were 12th-13th years old. with sampling techniques i.e. purposive sampling. Instruments that is used in this research is description test which was arranged based on mathematical problem solving skills material. Data analysis technique is with N-Gain T-test. The result show that the significant N-Gain score obtained is 0.008. The N-Gain score is smaller tha (α = 0.05), which means that there is a significant difference in the increase in mathematical problem solving abilities toward participant student who use mathematical habits of mind strategies with those using conventional learning. statistically proven habits of mind strategy that influences problem solving can be one of the practitioners' choices in teaching mathematics in basic education.